Derivatives of the triaminoguanidinium ion, 5. Acylation of triaminoguanidines leading to symmetrical tris(acylamino)guanidines and mesoionic 1,2,4-triazolium-3-aminides - Szabo, Jan; Greiner, Julian; Maas, Gerhard (Beilstein Journal of Organic Chemistry, 2017)
Depending on the reaction conditions, N,N’,N’’-tris(benzylamino)guanidinium salts can react with carboxylic acid chlorides to form either symmetrical N,N’,N’’-tris(N-acyl-N-benzylamido)guanidines 6 or mesoionic 4-amino-1,2,4-triazolium-3-hydrazinides 7. The latter were converted into 1,2,4-triazolium salts by protonation or methylation at the hydrazinide nitrogen atom. Neutral 1,2,4-triazoles 10 were obtained by catalytic hydrogenation of an N-benzyl derivative. Crystal structure analyses of a 4-benzylamino-1,2,4-triazolium-3-hydrazinide and of two derived 1,2,4-triazolium salts are presented.
Keywords: guanidines; mesoionic compounds; triaminoguanidinium salts; 1,2,4-triazolium-3-aminides